MANAGING DIGITAL MEDIA PRODUCTION THROUGH INTELLIGENT AUTOMATION - Chauhan, Garima; Sudan, Prerak; Vashisht, Nitish; Reddy BN, Krishna; Kaur, Gurpreet; Kumar S, Ashok; Sule, Bipin (ShodhKosh: Journal of Visual and Performing Arts, 2025)
The digital media sphere of production has blistered, which has led to the increase of the complexity of workflow, the presence of lower response time and the quality of the obtained output. The latest addition of intelligent automation in terms of artificial intelligence (AI) and machine learning (ML) has become the new game changer that can change the traditional production pipelines. The paper will also consider the application of smart automation to every stage of production process of digital media, such as the pre-production, production and post-production and how it can be applied to achieve the maximum efficiency, waste minimization, and creativity. Based on an analysis of the current automation models and systems, the paper explains how technologies such as natural language processing, computer vision, predictive analytics, and so forth can streamline processes, such as scriptwriting, camera control, editing, and even visual effects. Through the case studies of films, TV channels and content delivery websites, the paper gives examples of actual real-life applications of such tools as Adobe Sensei, Runway ML and Synthesia to automate the processes in the media industry without compromising the creative process. Moreover, the research touches upon the theoretical and ethical issues, as the problem is the dilemma of human creativity and algorithms. It also discusses the issues of intellectual property, data security, and workforce revolution in the creative industry.